Engaging learners in non-formal Science Technology Engineering and Mathematics education: ESKOM EXPO for Young Scientists - Dookie, Nalini; James, Angela (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
In the global arena, citizens should have the necessary knowledge and skills to be constructively engaged in the development of their country. Their experiences with science, technology, engineering and mathematics, (STEM) education is viewed as providing the skills for the professions of the future. In the non-formal education sector learners are engaged with science expos, which focusses on inquiry and project-based learning, in authentic science experiences and independent research to solve real-life problems by asking questions, collecting, evaluating, interpreting data, engaging and communicating argument with evidence from findings. The nature of the engagements varies across the grades and disciplines, even though there is consistency in the assessment formats and expectations of all learners re the planning and submission of projects.